Ethnopharmacological Effects of Urtica dioica, Matricaria chamomilla, and Murraya koenigii on Rotenone-Exposed D. melanogaster: An Attenuation of Cellular, Biochemical, and Organismal Markers - Shabnam Shabir; Sumaira Yousuf; Sandeep Kumar Singh; Emanuel Vamanu; Mahendra P. Singh (MDPI AG, 2022)
Natural antioxidants derived from plants have been proven to have significant inhibitory effects on the free radicals of living organisms during actively metabolization. Excessive production of free radicals increases the risk of neurodegenerative diseases, such as Alzheimer's disease, Parkinson's disease, and motor sclerosis. This study aimed to compare the ethnopharmacological effects of Urtica dioica (UD), Matricaria chamomilla (MC), and Murraya koenigii (MK) on the amelioration of rotenone-induced toxicity in wild-type Drosophila melanogaster (Oregon R+) at biochemical, cellular, and behavioral levels. Phytoextracts were prepared from all three plants, i.e., UD, MC, and MK (aqueous and ethanolic fractions), and their bioactive compounds were evaluated using in vitro biochemical parameters (DPPH, ABTS, TPC, and TFC), UV-Vis, followed by FT-IR and HPLC. Third instar larvae and freshly eclosed flies were treated with 500 µM rotenone alone or in combination with UD, MC, and MK for 24 to 120 h. Following exposure, cytotoxicity (dye exclusion test), biochemical (protein estimation and acetylcholinesterase inhibition assays), and behavioral assays (climbing and jumping assays) were performed. Among all three plant extracts, MK exhibited the highest antioxidant properties due to the highest TPC, TFC, DPPH, and ABTS, followed by UD, then MC. The overall trend was MK > UD > MC. In this context, ethnopharmacological properties mimic the same effect in Drosophila, exhibiting significantly (p < 0.05) reduced cytotoxicity (trypan blue), improved biochemical parameters (proteotoxicity and AChE activity), and better behavioral parameters in the organisms cotreated with phyto extracts compared with rotenone. Conclusively, UV-Vis, FTIR, and HPLC analyses differentiated the plant extracts. The findings of this research may be beneficial in the use of select herbs as viable sources of phyto-ingredients that could be of interest in nutraceutical development and various clinical applications.